2013
DOI: 10.1111/anae.12312
|View full text |Cite
|
Sign up to set email alerts
|

A randomised study of intranasal dexmedetomidine and oral ketamine for premedication in children

Abstract: SummaryWe studied the effects of intranasal dexmedetomidine combined with oral ketamine for premedication in children. One hundred and sixty children aged between 2 and 6 years were randomly allocated to one of four groups: 1 lg.kg À1 intranasal dexmedetomidine with 3 mg.kg À1 oral ketamine (Group 1); 1 lg.kg À1 intranasal dexmedetomidine with 5 mg.kg À1 oral ketamine (Group 2); 2 lg.kg À1 intranasal dexmedetomidine with 3 mg.kg À1 oral ketamine (Group 3); and 2 lg.kg À1 intranasal dexmedetomidine with 5 mg.kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 24 publications
(27 reference statements)
1
27
0
Order By: Relevance
“…In a study where 80 pediatric patients were given oral ketamine 6 mg/kg, 18% developed ED, much lower than the 56% reported in the placebo group [76]. These results coincided with a randomized clinical trial by Eghbal et al, which determined low dose ketamine during induction of anesthesia improved both emergence agitation and postoperative pain following adenotonsillectomy in children [79]. Similarly, Abu-Shahwan and Chowdary's randomized double blind study of 85 children aged 4-7 years demonstrated that treatment with ketamine 0.25 mg/kg decreased the incidence of emergence agitation [77].…”
Section: Ketaminesupporting
confidence: 59%
See 1 more Smart Citation
“…In a study where 80 pediatric patients were given oral ketamine 6 mg/kg, 18% developed ED, much lower than the 56% reported in the placebo group [76]. These results coincided with a randomized clinical trial by Eghbal et al, which determined low dose ketamine during induction of anesthesia improved both emergence agitation and postoperative pain following adenotonsillectomy in children [79]. Similarly, Abu-Shahwan and Chowdary's randomized double blind study of 85 children aged 4-7 years demonstrated that treatment with ketamine 0.25 mg/kg decreased the incidence of emergence agitation [77].…”
Section: Ketaminesupporting
confidence: 59%
“…Debate about the efficacy of ketamine in the management of ED is largely driven by earlier studies that linked ketamine to an increased risk of ED [1,[73][74][75]. However, more recent studies have contradicted these findings [76][77][78][79]. In a study where 80 pediatric patients were given oral ketamine 6 mg/kg, 18% developed ED, much lower than the 56% reported in the placebo group [76].…”
Section: Ketaminementioning
confidence: 99%
“…Previous studies have shown that intranasal dexmedetomidine is an effective way to sedate children . It is relatively easy to administer and has a higher bioavailability .…”
Section: Discussionmentioning
confidence: 99%
“…In our experience, children often refused to receive a second dose of chloral hydrate, probably due to its bitter caustic taste, whereas all children showed good tolerance to intranasal administration of dexmedetomidine. Previous studies have shown that intranasal dexmedetomidine is an effective way to sedate children (9,26). It is relatively easy to administer and has a higher bioavailability (27).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is cur-rently not licensed for administration by this route it has proved successful both as a premedicant and as a sedative for nonpainful procedures. Jia et al studied childen who were administered combinations of intranasal dexmedetomidine and oral ketamine in a variety of doses [19]. They concluded that 2 lg.kg À1 intranasal dexmedetomidine together with 3 mg.kg À1 oral ketamine was the optimal combination, with children being easily separated from their parent, accepting intravenous cannulation and there were no excessive side-effects or postoperative complications.…”
Section: Choice Dose and Mode Of Administration Of Sedative Agentsmentioning
confidence: 99%